Effects of ambient temperature on physiological responses to incremental exercise test - Tyka, A.; Wiecha, S.; Palka, T.; Szygula, Z.; Tyka, A.; Cison, T. (Journal of Human Kinetics, 2010)
Physiological variables are regularly analyzed by coaches and sport scientists during an incremental exercise test (IET) until exhaustion. Physiological and biochemical responses of the body are modified upon exercising in the heat as well as results obtained in the IET. Heat changes the validity of these results to be used when prescribing or monitoring training processes and predicting performance in athletes To determine the effect of ambient temperature on physiological responses, twelve physically active men completed IET on the cycle ergometer in three ambient temperatures: 23°C (T23), 31°C (T31) and 37°C (T37). We measured continuously: rectal temperature (Tre) and aural canal temperature (Tac), heart rate (HR), 2 V&O , 2 V& CO , respiratory rate (RR), tidal volume (TV), and minute ventilation (VE). Blood samples for pl LA- were taken before, at the end of each exercise step and 3 minutes after the test ended. The exercise duration (DE) and energy expenditure (EE) to reach the threshold of decompensated metabolic acidosis (TDMA) decreased (p<0.05) in T31 (11.27 ± 3.03 minutes; 86.2 ± 24.2 kJ) and T37 (10.72 ± 2.76 minutes; 79.5 ± 21.3 kJ) in comparison to T23 (13.10 ± 2.30 minutes; 108.8 ± 23.9 kJ), with no differences observed in pl LA- , VE, 2 V&O or Tre. We observed an increase (p<0.05) in pl LA- after tests in T31 (11.08 ± 1.89 mmol/L) and T37 (11.94 ± 2.25 mmol/L) in comparison to T23 (10.26 ± 2.30 mmol/L), with no differences observed in 2 V&O max, end Tre, EE and DE to exhaustion. The TDMA occurs faster and at a lower WL, while performing IET in 31°C and 37°C. Coaches sport scientists should consider these factors when conducting IET to assess the threshold level and performance of athletes.